Chronic fluoxetine treatment in socially-isolated rats modulates the prefrontal cortex synaptoproteome - Filipović, Dragana; Novak, Božidar; Xiao, Jinqiu; Yan, Yu; Bernardi, Rick E.; Turck, Christoph W. (Journal of proteomics, 2023)
Exposure to chronic social isolation (CSIS) and synapse dysfunction have been implicated in the etiology of major depressive disorder (MDD). Fluoxetine (Flx) has been widely used to treat MDD, but its mechanisms of action remain elusive. We employed comparative synaptoproteomics to investigate the changes in the levels of proteins and molecular signaling pathways in prefrontal cortical samples of adult male Wistar rats exposed to CSIS, a rat model of depression, and CSIS rats treated with chronic Flx and controls, using liquid chromatography coupled to tandem mass spectrometry. Flx-treated control rats showed a decreased level of proteins involved in vesicle-mediated transport, and a predominantly increased level of exocytosis-associated proteins. CSIS significantly reduced the level of proteins involved in the ATP metabolic process, clathrin-dependent endocytosis, and proteolysis. Flx treatment in CSIS rats stimulated synaptic vesicle trafficking by increasing the regulation of exo/endocytosis-associated proteins, proteins involved in synaptic plasticity including neurogenesis, Cox5a, mitochondria-associated proteins involved in oxidative phosphorylation, and ion transport proteins (Slc8a2, Atp1b2). Flx treatment resulted in an increased synaptic vesicle dynamic, plasticity and mitochondrial functionality, and a suppression of CSIS-induced impairment of these processes. - Biological significance - Identifying biomarkers of MDD and treatment response is the goal of many studies. Contemporary studies have shown that many molecular alterations associated with the pathophysiology of MDD reside within the synapse. As part of this research, a growing importance is the use of proteomics, as monitoring the changes in protein levels enables the identification of (possible) biochemical pathways and processes of importance for the development of depressive-like behavior and the efficacy of antidepressant treatments. We profiled proteomic changes representative of the development of CSIS-induced depressive-like behavior and the antidepressant effects of Flx. Our study has identified synaptosomal proteins and altered molecular pathways that may be potential markers of prefrontal cortical synaptic dysfunction associated with depressive-like behavior, and further clarified the mechanisms of depressive-like behavior and mode of action of Flx. Our findings indicate potential PFC synaptic targets for antidepressant treatment.
Online verfügbar 8. Mai 2023, Artikelversion 10. Mai 2023
Gesehen am 24.07.2023